Studious Drift Movements and Protocols for a Postdigital Education - Hyland, Peter (University of Minnesota Press, 2022)
What kind of university is possible when digital tools are not taken for granted, but hacked for a more experimental future?The global pandemic has underscored contemporary reliance on digital environments. This is particularly true among schools and universities, which, in response, shifted much of their instruction online. Because the rise of e-learning logics, ed-tech industries, and enterprise learning-management systems all threaten to further commodify and instrumentalize higher education, these technologies and platforms have to be creatively and critically struggled over. Studious Drift intervenes in this struggle by reviving the relationship between studying and the generative space of the studio in service of advancing educational experimentation for a world where digital tools have become a permanent part of education. Drawing on Alfred Jarry's pataphysics, the "science of imaginary solutions," this book reveals how the studio is a space-time machine capable of traveling beyond the limits of conventional online learning to redefine education as interdisciplinary, experimental, public study.